The Geodemographic Distribution of Caries Experience in Neighboring Fluoridated and Nonfluoridated Populations - Martin Tickle, PhD; Keith M. Milsom, MSc; Tony M. Jenner, MSc; Anthony S. Blinkhorn, PhD (Blackwell Synergy, 2003)
This study compares the geodemographic distribution of caries experience in neighboring fluoridated and nonfluoridated populations